2018
DOI: 10.1007/s00784-018-2771-9
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival lipid A profile and endotoxin activity in periodontal health and disease

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…To demonstrate clinical feasibility, a skin swab was collected and subsequently centrifuged to collect cells and debris, which was then diluted and injected into the flow system, and the low-abundant protein was detected and quantified (Ertürk et al, 2018). As another example, in 2019 Strachan et al used mass spectrometry to analyse the lipid A isoforms of bacteria in the subgingival plaque of individuals before and after treatment for periodontitis (Strachan et al, 2019). Certain prominent peaks not present in samples from healthy individuals were visible in samples from diseased patients, corresponding to overly phosphorylated and acetylated lipid A isoforms, and these peaks disappeared after periodontal treatment (Strachan et al, 2019).…”
Section: Biosensors For Indirect Microbiome Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate clinical feasibility, a skin swab was collected and subsequently centrifuged to collect cells and debris, which was then diluted and injected into the flow system, and the low-abundant protein was detected and quantified (Ertürk et al, 2018). As another example, in 2019 Strachan et al used mass spectrometry to analyse the lipid A isoforms of bacteria in the subgingival plaque of individuals before and after treatment for periodontitis (Strachan et al, 2019). Certain prominent peaks not present in samples from healthy individuals were visible in samples from diseased patients, corresponding to overly phosphorylated and acetylated lipid A isoforms, and these peaks disappeared after periodontal treatment (Strachan et al, 2019).…”
Section: Biosensors For Indirect Microbiome Analysismentioning
confidence: 99%
“…As another example, in 2019 Strachan et al used mass spectrometry to analyse the lipid A isoforms of bacteria in the subgingival plaque of individuals before and after treatment for periodontitis (Strachan et al, 2019). Certain prominent peaks not present in samples from healthy individuals were visible in samples from diseased patients, corresponding to overly phosphorylated and acetylated lipid A isoforms, and these peaks disappeared after periodontal treatment (Strachan et al, 2019). These examples highlight the ability of biosensors to extract meaningful information from human microbial communities, which can be applied to diagnose disease states and monitor treatment outcome.…”
Section: Biosensors For Indirect Microbiome Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Dental plaque or biofilm is composed of microcolonies of bacterial cells, nonrandomly distributed in a shaped matrix or glycocalyx, which subsequently mineralizes to form calculus (Kumar, Swarga Jyoti, Sonowal, & Chawla, 2015). Periodontopathogenic bacteria secrete lipopolysaccharide (LPS), an endotoxin which is absorbed by the most superficial layer of root cementum (Aspriello, Piemontese, Levrini, & Sauro, 2011;Gibbons, 1989;Strachan et al, 2018). Aleo, De Renzis, and Faber (1975) indicated that human gingival fibroblasts did not adhere in vitro to a root surface contaminated with LPS, and assessed that this was possible only when the cementum was removed by root planing.…”
Section: Introductionmentioning
confidence: 99%
“…Nas bactérias Gram positivas, destaca-se o ácido lipoteicóido (lipoteichoic acid -LTA) e nas Gram negativas, uma endotoxina denominada lipopolissacarídeo (lipopolysaccharide -LPS) (Siqueira et al, 2002;Staquet et al, 2011). O LPS é um complexo glicolipídico composto por um polissacarídeo hidrofílico e um domínio hidrofóbico, conhecido como lípide A, responsável pelos efeitos biológicos desta endotoxina (Strachan et al, 2019). As bactérias Gram negativas são comumente encontradas em polpas necróticas, sendo os principais microrganismos envolvidos em infecções endodônticas (Fabricius et al, 1982;Morrison;Ryan, 1987).…”
Section: Scaps E Lipopolissacarídeo (Lps)unclassified